KEPEMIMPINAN MILENIAL: SUDUT PANDANG MAHASISWA FAKULTAS EKONOMIKA DAN BISNIS UNTAG SEMARANG - Amsar Amsar; Hasyim Hasyim (STIE Pelita Nusantara Semarang, 2022)
Worries about the attitudes and leadership characteristics of the young generation, commonly called the Millennial Generation today, where they are compatible with digital, they tend to focus their attention on their daily lives and are very dependent on cellphones. All needs are carried out through these facilities, this is not only a means of providing convenience but not least it has an impact on the behavior of the current Millennial generation, there is a perception that the current generation is the lazy generation and this will also raise concerns about weakening the attitude of caring for others. . Will the future leaders of the Indonesian nation give birth to leaders who no longer care about the worries, difficulties and life of this nation?Leadership is one of the most important keys to effective and successful business goals. Leadership quality refers to the success or failure of an organization. 4.0 Managing the industrial revolution is a challenge in itself, as Indonesia's millennial population has become very flexible in their daily lives as a result of information technology. This often affects the digital transition.The study in this research is about Millennial Leadership: Student Perspective of the Faculty of Economics and Business Untag Semarang. The issues raised are: (1) Is there a joint correlation between Digital Thinking; Good Observer and Listener; Courage to Make Decisions; and Never Give Up in Millennial Leadership, (2) Is there a partial correlation between indicators in Digital Thinking; Good Observer and Listener; Courage to Make Decisions; and Never Give Up in Millennial Leadership?The experimental model used in this study, which resulted in a relationship between numerical thinking and intelligent listeners and students with a combined grade of 0.489, indicates a high level or relationship between the two variations. A coordination score of 0.460 was better than the two coordinates or the rate of change; and the correlation between technical thinking and impermissibility is 0.418, which means that the two variables are related or mutually related.